2011
DOI: 10.1007/s00382-011-1080-7
|View full text |Cite
|
Sign up to set email alerts
|

Climate change projections and stratosphere–troposphere interaction

Abstract: Climate change is expected to increase winter rainfall and flooding in many extratropical regions as evaporation and precipitation rates increase, storms become more intense and storm tracks move polewards. Here, we show how changes in stratospheric circulation could play a significant role in future climate change in the extratropics through an additional shift in the tropospheric circulation. This shift in the circulation alters climate change in regional winter rainfall by an amount large enough to signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
155
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 34 publications
11
155
0
1
Order By: Relevance
“…Such non-CO 2 forcings -particularly those that warm the mid-latitudes and are underestimated by most models (e.g., Ramanathan and Carmichael, 2008;Koch et al, 2009) -may help explain the discrepancy between modeled and observed estimates of recent tropical expansion. Moreover, a recent study by Scaife et al (2012) found increased CO 2 in GCMs with a well-resolved stratosphere yielded an equatorward storm track shift, particularly over the Atlantic during winter. This implies the observed poleward shift may be due more to heterogeneous warming agents, as opposed to greenhouse gases.…”
Section: Discussionmentioning
confidence: 94%
“…Such non-CO 2 forcings -particularly those that warm the mid-latitudes and are underestimated by most models (e.g., Ramanathan and Carmichael, 2008;Koch et al, 2009) -may help explain the discrepancy between modeled and observed estimates of recent tropical expansion. Moreover, a recent study by Scaife et al (2012) found increased CO 2 in GCMs with a well-resolved stratosphere yielded an equatorward storm track shift, particularly over the Atlantic during winter. This implies the observed poleward shift may be due more to heterogeneous warming agents, as opposed to greenhouse gases.…”
Section: Discussionmentioning
confidence: 94%
“…Despite some contradictory results obtained with different GCMs (Scaife et al, 2012), there are several studies confirming that drought frequency is increasing in the Mediterranean basin (Seneviratne et al, 2006;Sousa et al, 2011;Hoerling et al, 2012), in particular over the IP (Xoplaki et al, 2012;Trigo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This low confidence is related to concerns over the skill of many models in realistically representing large-scale features such as the stratosphere (Scaife et al 2012;Manzini et al 2014) and ocean circulation as well as the dynamics of individual storm systems, for example due to insufficient horizontal resolution (Willison et al 2013). Consequently, the consensus between different models on a climate change signal remains rather low (Harvey et al 2012;Zappa et al 2013b).…”
mentioning
confidence: 99%